PENGARUH RELATIONSHIP MARKETING TERHADAP LOYALITAS NASABAH BANK - Sugeng Pradikto (Jurnal Keuangan dan Perbankan, 2008)
For banking world, the existence of customers was as important asset. In the middleof strict and dynamic competition, Bank Mandiri as one of financial service providers wasaware that customers loyalty was what should be obtained and maintained. One way appliedby Bank Mandiri as financial service provider was relationship marketing strategy. Marketingstrategy focussed on building relationship with the customers had final objective namely toobtain customers loyalty, with the purpose that these customers could provide long termadvantages for the company. This study was conducted on the customers of Tabungan Mandiriin PT. Bank Mandiri (Persero) Branch of Pasuruan. The technique of data collection wasquestionnaire. The number of population was 10,627 customers. The number of sample was73 with simple random sampling technique. Data analysis applied regression analysis. Basedon the description on the result of the study above, it could be concluded that there waspositive and significant effects of variables service quality, commitment and communicationeither partially or simultaneously toward customers loyalty. Concerning the result of the study,it was suggested (1) to improve the service especially physical development or banking hallwhich should be conducted continuously in order to make customers satisfied in transaction.(2) to have more socialization on the use of Internet Banking Mandiri and SMS Banking Mandiritechnology in order to two ways communication between customers and Bank Mandiri.